Infectious Disease Behaviour Resulting In a Public Health Catastrophe - Bruce Masonova SOLOZAFY BEMENA Bruce; , André TOTOHASINA; FENO Daniel Rajaonasy (Lembaga Sembilan Tiga Community, 2022)
In epidemiology, the search for new behavior of infectious agents, processes, andmechanisms of diffusion of infection of emerging infectious diseases caused by global warminghas already led to tangible results. This paper proposes a dynamic endemic model Susceptible,Exposed, Precontaged, Infected, Retired, Susceptible (SEPIRS). This model is specialized in epidemics that persist for a long time and in cases where the infection spreads directly: first betweenpre-contagious individuals (asymptomatic) and susceptible individuals, second between infectiousindividuals (symptomatic) and susceptible individuals. This model characterizes the individual recovering from infection to develop a temporary immunity and then become susceptible againafter some time.